Several Fixed-Point Theorems for F-Contractions in Complete Branciari b-Metric Spaces and Applications. (25th November 2020) - Chen, Lili; Huang, Shuai; Li, Chaobo; Zhao, Yanfeng
Abstract : In this paper, we prove the existence and uniqueness of fixed points for F -contractions in complete Branciari b - metric spaces. Furthermore, an example for supporting the related result is shown. We also present the concept of the weak well-posedness of the fixed-point problem of the mapping T and discuss the weak well-posedness of the fixed-point problem of an F -contraction in complete Branciari b -metric spaces. Besides, we investigate the problem of common fixed points for F -contractions in above spaces. As an application, we apply our main results to solving the existence and uniqueness of solutions for a class of the integral equation and the dynamic programming problem, respectively.